Residual Stress Profiling of Sub-surface Treated Nickel-Based Superalloy using Electromagnetic NDE Method - Annamalai, Swaminathan (2017)
To evaluate the whole residual stress profile of sub-surface processes, existing methods such as X-ray diffraction (XRD) or central hole drilling method (CHD) require material removal, which is inherently destructive. A non-destructive residual stress measurement method using eddy current is utilized to capture the stress depth profile. The technique is demonstrated on nickel-based superalloy Inconel 100 (IN100) treated using deep cold rolling and shot peening to show that the method developed for stress profiling can be independent of the sub-surface treatment. This paper presents the experimental results obtained with an experimental set-up based on the commercially available Nortec eddy current instrument and pencil surface probes. Test samples prepared from IN100 by deep cold rolling and shot peening for two different treatment conditions will be presented. The calculated residual stress profile using eddy current (EC) is compared with the equivalent residual stress profile using CHD for penetration depths from (100-550)µm to validate the measurement technique.